Planning, implementation and evaluation of a positive body image exercise program for women : an acceptability and feasibility study - Raninen, Hanna-Kaisa (2019)
Body image refers to the perceptions, feelings and thoughts that a person has about his or her body. Body dissatisfaction is common among women in Western societies and can lead to lower psychological functioning, lower exercise motivation, compulsive exercise, disordered eating and generally to a lower quality of life. However, very little research exists on how to support positive body image in training in general or specifically in the personal training context. The current research is a mixed-method action research case study that explored the feasibility and acceptability of a 10-week ”Strong Woman” -training program within female participants (n=4) and a coach. The aim of the program was to support positive body image and encourage women to train with weights. The program focused on body functionality rather than appearance. The program consisted of weight training focusing on body functionality, body image supporting coach modeling and communication, peer support, body functionality and body awareness writing exercises, a training diary, breathing exercises and a calm, mirrorless training environment as well as voluntary body measurement taking. Assembled through a researcher’s journal and participant feedback, a thorough description of the program and its individual components is provided. The program was able to be carried out as planned and was very well accepted among the participants and the coach who led training. All the participants liked the program and would like to recommend it to other people. They felt that the program was able to encourage a more gentle attitude towards their bodies. In addition, the participants felt the program was easy to participate in and that they are going to utilize the things they learned in the program in the future. Based on the qualitative analysis of the interviews and the researcher’s journal, the psychologically safe environment created by the coach, sense of community and peer support were the most valuable parts of the program. This study showed that it was possible to implement the program successfully to a group of 4 female participants. The program can be implemented as such or parts of it can be utilized by sport and exercise professionals coaching athletes or the general public.